2017
DOI: 10.7196/samj.2017.v107i10.12833
|View full text |Cite
|
Sign up to set email alerts
|

User perspectives on Implanon NXT in South Africa: A survey of 12 public-sector facilities

Abstract: Background. Implanon NXT, a long-acting reversible contraceptive, was introduced in South Africa (SA) in early 2014, aiming to expand the method mix and increase its effectiveness. Initial uptake was high, but has since declined considerably. In these early years after the implant's introduction, it is important to identify reasons for the decline, and remedy gaps in services. Objectives. To determine periods of use, reasons for the use and early removal of the implant Implanon NXT. Methods. In 2016, we recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 22 publications
5
82
0
Order By: Relevance
“…[30] SA data also indicate that training that is too short and does not include management of side-effects and removals, may be inadequate to support implant provision. [31,32] Pre-insertion counselling and ongoing support Adopt a 'LARC first' structured approach to contraceptive counselling. The content of contraceptive counselling heavily influences method selection, especially among younger women.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…[30] SA data also indicate that training that is too short and does not include management of side-effects and removals, may be inadequate to support implant provision. [31,32] Pre-insertion counselling and ongoing support Adopt a 'LARC first' structured approach to contraceptive counselling. The content of contraceptive counselling heavily influences method selection, especially among younger women.…”
Section: Fy 2015 Fy 2016 Fy 2017mentioning
confidence: 99%
“…This was not always the case, as pointed out by Pillay et al [3] in this issue of SAMJ. For example, only about half of the clients interviewed in Johannesburg and the North West Province recalled being warned about side-effects, the principal cause of implant discontinuation.…”
Section: Counselling and Choicementioning
confidence: 74%
“…In many settings, the implant is considered as 'first-line' for women within 48 hours of childbirth or after an abortion, as well as for adolescents and young women. [6,[11][12][13] The study by Pillay et al, [3] however, found no evidence that the youth were being targeted; only ~15% of participants were aged 18 -24 years, the age group with the highest unmet need for contraception. [1,14] Targeted implant provision is needed and creative approaches are called for.…”
Section: Counselling and Choicementioning
confidence: 99%
See 2 more Smart Citations